Potential use of wastewater in agriculture - Mendoza-Retana, Sarai Shesareli; Cervantes-Vázquez, María Gabriela; Valenzuela-Garcia, Ana Alejandra; Guzmán-Silos, Tania Lizzeth; Orona-Castillo, Ignacio; Cervantes-Vázquez, Tomás Juan Álvaro (Revista Mexicana de Ciencias Agrícolas, 2021)
The contamination of water, air, soil and food is a collateral consequence of the activities that man has developed to live and improve his quality of life. The development of the human being, its continuous growth since the time of the industrial revolution has left damage and degradation in natural resources. In its demographic, scientific and technological growth, human beings have not made sufficient efforts to sustainably preserve natural resources. Among these resources, water is one of the most essential and vital for all forms of life, but every day the resource is scarcer in a healthy way. Due to multiple factors associated with population growth, urbanization and industrialization, all equally direct and indirect causes of climate change. Treating and using wastewater is challenging because that is often the only option farmers have. Thus, these waters represent a valuable resource, both from an economic and environmental point of view (conservation of water resources, recycling of nutrients). Currently, about 80% of wastewater is disposed of without treatment and is used for agricultural irrigation, representing a significant sanitary problem (due to the presence of pathogenic and toxic elements).